[BTBA]Cl-FeCl3 as an Efficient Lewis Acid Ionic Liquid for the Synthesis of Perimidine Derivatives. Issue 6 (2nd June 2016) - Bahrami, Kiumars; Saleh, Sepideh
Abstract : An effective synthesis of various biologically important 2, 3-dihydroperimidines from reaction of aldehydes and naphthalene-1, 8-diamine has been developed using [BTBA]Cl-FeCl3 as an efficient Lewis acid ionic liquid. This method is a very simple and high yielding reaction for the preparation of the titled compounds. Different functional groups are tolerated under this reaction conditions including ether, phenol, amine, and alkene.